CONFLICT BETWEEN LEGAL NORMS AND COMMUNITY TRADITIONS: LAW ENFORCEMENT AGAINST ACTS OF VIOLENCE AND ANIMAL ABUSE IN THE BULL RACING TRADITION - Devi Nadhilah,; Abraham Ferry Rosando, (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2025)
The Karapan Sapi tradition is a cultural heritage of the Madurese people that has high social and economic value. However, in its implementation, acts of violence against the oxen occur, which are legal violations that still continue to this day. This research discusses criminal responsibility for acts of violence and animal abuse in Karapan Sapi, to find out the government’s efforts and forms of protection for animals in the implementation of Karapan Sapi. This research uses a normative juridical method with a conceptual and statute approach to examine laws and regulations related to the issue. The results show that law enforcement is still not implemented even though regulations prohibiting violence against animals already exist, such as the Instruction of the Governor of East Java Number 1 of 2012 concerning Karapan Sapi Without Violence, Law Number 41 of 2014, and Government Regulation Number 95 of 2012 regarding animal welfare. This research is expected to raise public awareness and encourage legal reform to ensure animal welfare from violent and abusive behavior.